Response of Medical Cannabis (Cannabis sativa L.) to Nitrogen Supply Under Long Photoperiod - Avia Saloner; Avia Saloner; Nirit Bernstein (Frontiers in Plant Science, 2020)
The development progression of medical cannabis plants includes a vegetative growth phase under long photoperiod, followed by a reproductive phase under short photoperiod. Establishment of plant architecture at the vegetative phase affects its reproduction potential under short photoperiod. Nitrogen (N) is a main component of many metabolites that are involved in central processes in plants, and is therefore a major factor governing plant development and structure. We lack information about the influence of N nutrition on medical cannabis functional-physiology and development, and plant N requirements are yet unknown. The present study therefore investigated the developmental, physiological, and chemical responses of medical cannabis plants to N supply (30, 80, 160, 240, and 320 mgL−1 N) under long photoperiod. The plants were cultivated in an environmentally controlled growing room, in pots filled with soilless media. We report that the morpho-physiological function under long photoperiod in medical cannabis is optimal at 160 mgL−1 N supply, and significantly lower under 30 mgL−1 N, with visual deficiency symptoms, and 75 and 25% reduction in plant biomass and photosynthesis rate, respectively. Nitrogen use efficiency (NUE) decreased with increasing N supply, while osmotic potential, water use efficiency, photosynthetic pigments, and total N and N-NO3 concentrations in plant tissues increased with N supply. The plant ionome was considerably affected by N supply. Concentrations of K, P, Ca, Mg, and Fe in the plant were highest under the optimal N level of 160 mgL−1 N, with differences between organs in the extent of nutrient accumulation. The majority of the nutrients tested, including P, Zn, Mn, Fe, and Cu, tended to accumulate in the roots > leaves > stem, while K and Na tended to accumulate in the stem > leaves > roots, and total N, Ca, and Mg accumulated in leaves > roots > stem. Taken together, the results demonstrate that the optimal N level for plant development and function at the vegetative growth phase is 160 mgL−1 N. Growth retardation under lower N supply (30–80 mgL−1) results from restricted availability of photosynthetic pigments, carbon fixation, and impaired water relations. Excess uptake of N under supply higher than 160 mgL−1 N, promoted physiological and developmental restrictions, by ion-specific toxicity or indirect induced restrictions of carbon fixation and energy availability.